Structures of microbial communities found in anaerobic batch runs that produce methane from propionic acid-Seeded from full-scale anaerobic digesters above a certain threshold - Kim, Woong; Shin, Seung Gu; Han, Gyuseong; Cho, Kyungjin; Hwang, Seokhwan (Elsevier BV, 2015)
The volatile fatty acid propionate inhibits anaerobic digestion during organic waste treatments. To examine potential microbial interactions that accelerate propionate oxidation, anaerobic digestion systems seeded with various types of anaerobic sludge were analyzed. Seed samples were collected from 10 different full-scale anaerobic reactors in South Korea. Propionate oxidation was estimated as the methane production rate per gram of propionate used per day. Two domestic sewage sludge showed the highest methane production rate values, 109.1 +/- 4.2 and 74.5 +/- 8.6 mL CH4/(g propionate.d). A food waste recycling wastewater source exhibited the lowest methane production rate, 33.2 +/- 2.6 mL CH4/(g propionate.d). To investigate how the microbial community structure affected propionate oxidation, qualitative molecular analyses were carried out using denaturing gradient gel electrophoresis. Methanosaeta concilii, an aceticlastic methanogen, was detected in most batch runs. Smithella propionica, a unique propionate oxidizer and simultaneous producer of acetate, was found in domestic sewage sludge sources showing the highest methane production rate; in contrast, Desulfobulbus rhabdoformis, a sulfate reducer coupled with the consumption of acetate to be used as a precursor of methane, was observed in food waste recycling wastewater sludge source showing the lowest methane production rate. Thus, we propose that S. propionica, a syntrophic acetate producer using propionate, might cooperate with aceticlastic methanogens for high methane production during anaerobic digestion that included propionate. (C) 2015 Elsevier B.V. All rights reserved.